A multidisciplinary approach towards modeling of a virtual human lung - Timothy Lam; Henry T. Quach; Lauren Hall; Maria Abou Chakra; Amy P. Wong (npj Systems Biology and Applications)
Abstract Integrating biological data with in silico modeling offers the transformative potential to develop virtual human models, or “digital twins.” These models hold immense promise for deepening our understanding of diseases and uncovering new therapeutic strategies. This approach is especially valuable for diseases lacking reliable models. Here we review current modelling efforts in of human lung development, highlighting the role of interdisciplinary collaboration and key advances toward a digital lung twin.